ANALYSIS OF THE POSITIVE IMPACT OF DIGITAL TECHNOLOGIES ON THE MOTIVATION AND KNOWLEDGE OF STUDENTS IN THE DEVELOPMENT OF THE EDUCATIONAL PROCESS - Fayzullaeva, Madina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
In this article, you can get acquainted with the results of our experimental work on the extent to which digital technologies are actually used to accelerate the educational process in our country. This study mainly tested in English. The reason for this is that the attention paid to English as a foreign language in our country is growing year by year, as well as being able to easily get acquainted with the experiences of the developed countries of the world through the English language. Moreover, through this research, we tried to show the aspects that we do not pay attention to in the application of digital technologies to the educational process.